Kebijakan Dinas Perhubungan Kota Palangkaraya Dalam Penertiban Juru Parkir Liar Perspektif Siyasah Syar’iyah - Adnan, Muskhan; Syarifuddin, Syarifuddin; Ahmad, Sabarudin (Kamaya: Jurnal Ilmu Agama, 2025)
The development and enforcement of parking regulations in Palangka Raya is an ongoing effort aimed at increasing local revenue. To prevent the rise in illegal parking violations, the Palangka Raya City Transportation Agency is taking enforcement action. This research was conducted in Palangka Raya City using the Normative legal research method and Empirical legal research, as well as a descriptive qualitative approach. The results of this study indicate that parking supervision in the city of Palangka Raya has been running although not optimally, parking supervision is carried out by forming a special team that will supervise, monitor and control in the field every day and involve other agencies. as well as creating new innovations by including a fast and accurate supervision system using the Si-Takir application (Parking Arrangement System) to improve parking management and accountability, as well as public complaint tools. The Retribution Management System Based on Palangka Raya Mayor Regulation No. 24 of 2022 in organizing parking on the side of public roads can be managed directly by the Palangka Raya City Regional Government and/or can collaborate with individuals and/or business entities. Before the cooperation of individuals or business entities, the Palangka Raya City Regional Government through the Palangka Raya City Transportation Agency conducts a parking potential survey and makes technical considerations. Obstacles that can hinder and support the Palangka Raya City Transportation Agency in implementing the regulation of illegal parking violations on the road are weak citizen participation in maintaining order, or resistance to changes related to the values of discipline and collective responsibility, reflection of social ethics, public policy without the support of the community's moral culture will be difficult to implement optimally. From a sharia perspective, illegal parking management can be seen as a government policy, implemented through the Palangka Raya City Transportation Agency, aimed at realizing public welfare and preventing harm. The government has a responsibility to regulate and regulate public spaces, including roads and parking facilities. Controlling illegal parking is part of this responsibility.